Combined metabolomics and transcriptomics analysis of rats under neuropathic pain and pain-related depression - Xi, Caiyun; He, Liqiong; Huang, Zhifeng; Zhang, Jianxi; Zou, Kailu; Guo, Qulian; Huang, Changsheng (Frontiers in Pharmacology, 2023)
Neuropathic pain often leads to negative emotions, which in turn can enhance the sensation of pain. This study aimed to investigate the molecular mechanisms mediating neuropathic pain and negative emotions. Chronic constriction injury (CCI) rats were used as model animals and behavioral tests were conducted to assess pain and negative emotions. Then, the rat anterior cingulate cortex (ACC) was analyzed using UPLC-MS/MS and subsequently integrated with our previously published transcriptome data. Metabolomics analysis revealed that 68 differentially expressed metabolites (DEMs) were identified, mainly in amino acid metabolites and fatty acyls. Combined with our previously published transcriptome data, we predicted two genes that potentially exhibited associations with these metabolites, respectively Apolipoprotein L domain containing 1 (Apold1) and WAP fourdisulfide core domain 1 (Wfdc1). Taken together, our results indicated that peripheral nerve injury contributing to neuropathic pain and pain-related depression may be associated with these metabolites and genes. This research provides new insights into the molecular regulatory mechanism, which could serve as a reference for the treatment of neuropathic pain and pain-related depression.